2013
DOI: 10.1007/s12288-013-0269-9
|View full text |Cite
|
Sign up to set email alerts
|

Modified Irinotecan Plus Cisplatin and Dexamethasone (ICD) Combination Chemotherapy as Salvage Chemotherapy for Patients with Relapsed/Refractory Diffuse Large Cell Lymphoma

Abstract: About 50 % of patients with diffuse large cell lymphoma are candidate for salvage chemotherapy followed by bone marrow transplantation in the selected patients. In the current study we evaluated modified ICD (Irinotecan, Cisplatin, and Dexamethasone with G-CSF support) as salvage chemotherapy in the patients previously treated with R-CHOP or CHOP. In a retrospective study we evaluated 16 patients treated with modified ICD: irinotecan 65 mg/m 2 (max 100 mg)/day plus cisplatin 30 mg/m 2 (max 50 mg)/ day and dexa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…In 2002, a case report on the efficacy of Irinotecan in relapsed Hodgkin lymphoma demonstrated that Irinotecan has a therapeutic effect in patients with relapsed Hodgkin's lymphoma 18 . Moreover, Ghadiany et al evaluated the efficacy of Irinotecan in relapsed or refractory non-Hodgkin lymphoma 9 , 10 and Niitsu et al evaluated the efficacy of Irinotecan in relapsed or refractory peripheral T‐cell lymphoma with good results 19 . Therefore, we evaluated the effect of Irinotecan in combination with cisplatin and dexamethasone on Hodgkin lymphoma patients with promising results and low toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In 2002, a case report on the efficacy of Irinotecan in relapsed Hodgkin lymphoma demonstrated that Irinotecan has a therapeutic effect in patients with relapsed Hodgkin's lymphoma 18 . Moreover, Ghadiany et al evaluated the efficacy of Irinotecan in relapsed or refractory non-Hodgkin lymphoma 9 , 10 and Niitsu et al evaluated the efficacy of Irinotecan in relapsed or refractory peripheral T‐cell lymphoma with good results 19 . Therefore, we evaluated the effect of Irinotecan in combination with cisplatin and dexamethasone on Hodgkin lymphoma patients with promising results and low toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Irinotecan is a topoisomerase-I inhibitor and is used in many tumors. Ghadiany et al and Kang et al evaluated the efficacy of Irinotecan in relapsed or refractory non-Hodgkin lymphoma with an ORR of 81% and 71%, respectively 9 , 10 . Niitsu administered Irinotecan in combination with Mitoxantrone and dexamethasone in relapsed or refractory peripheral T‐cell lymphoma with an ORR of 60% 19 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations